Mathematical modelling and fuzzy knowledge-based decoupled control scheme for real-time interacting level control- MIMO system. (4th March 2023) - Nath, Ujjwal Manikya; Dey, Chanchal; Mudi, Rajani K.
ABSTRACT: Industrial processes are typically multi-input-multi-output (MIMO) in nature. The main challenge to control such processes is the interaction among the loops. In this study, primarily, the mathematical model of a practical quad-coupled tank process, i.e. MIMO by nature, consisting of two upper and two lower tanks, is identified. Subsequently, a fuzzy knowledge-based decoupler is designed for the identified model. Maintaining the water levels at desired heights for upper tanks in the presence of interactions and disturbances is the prime goal for this two-input-two-output (TITO) process. The proposed fuzzy decoupler combined with IMC-PID controllers is used to test the closed loop performance of the interacting coupled tank system. Real-time experimental results substantiate the effectiveness of the proposed scheme by providing enhanced performance toward maintaining the desired levels of the individual tanks, even in the presence of measurement noise.